Pectotibialis paghmanensis Tshernyshev gen. nov. – a new genus and species of soft-winged flower beetle (Coleoptera, Cleroidea, Malachiidae) from Afghanistan - Tshernyshev, Sergei E. (European Journal of Taxonomy, 2021)
A new genus with a new species of soft-winged flower beetle, Pectotibialis paghmanensis Tshernyshev gen. et sp. nov. are described from Afghanistan. The new genus can be distinguished from the congeners of the tribe Apalochrini by the dark pectination in the apices of tibiae in both sexes, and the anterior tibiae which are hollowed at distal half, flattened and rounded femora, bituberculate basal parts of head and pronotum, two lamellate metathoracic appendages, tarsal comb above second tarsomere of anterior legs, and serrate antennae in the male. Based on the metathoracic appendages and comb in anterior legs would attribute this new species to the new genus Dromanthomorphus Pic, 1921, but all the other above-mentioned characters define its independent status and the designation of a new genus; Pectotibialis Tshernyshev gen. nov. The external appearance, special male characters and genitalia of the type species of the new genus are illustrated, and a distribution map is provided. A key to the Apalochrus-section of the tribe Apalochrini is provided.